2017
DOI: 10.1063/1.4993741
|View full text |Cite
|
Sign up to set email alerts
|

Shockley-Read-Hall and Auger non-radiative recombination in GaN based LEDs: A size effect study

Abstract: GaN-based micro light-emitting diode (μLED) arrays are very promising devices for display applications. In these arrays, each μLED works as a single pixel of a whole image. The electro-optical performance of these μLEDs is an important subject to study. Here, we investigate the influence of LED size on the radiative and non-radiative recombination. The standard ABC model has been widely used to describe the efficiency of GaN based LEDs. Using this model, we extract A, B, and C coefficients for various LED size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
161
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 218 publications
(167 citation statements)
references
References 21 publications
4
161
2
Order By: Relevance
“…This specificity can be explained in the light of a typical curve ( Figure 2) showing evolution of External Quantum Efficiency (EQE) as a function of driving current density for a blue InGaN microLED. Evolution of EQE has been investigated thoroughly these last years and recently new models and interpretations have been found, in particular regarding size-dependent effects [9,10]. It is generally admitted that for lower current densities, EQE is impacted by non-radiative recombinations, resulting from defects at the periphery of the devices (Regime 1).…”
Section: Specificities Of Microleds Electro-optical Behaviormentioning
confidence: 99%
“…This specificity can be explained in the light of a typical curve ( Figure 2) showing evolution of External Quantum Efficiency (EQE) as a function of driving current density for a blue InGaN microLED. Evolution of EQE has been investigated thoroughly these last years and recently new models and interpretations have been found, in particular regarding size-dependent effects [9,10]. It is generally admitted that for lower current densities, EQE is impacted by non-radiative recombinations, resulting from defects at the periphery of the devices (Regime 1).…”
Section: Specificities Of Microleds Electro-optical Behaviormentioning
confidence: 99%
“…1 along with theoretical predictions according to the ABC model. The values of A, B, and C on size and peak wavelength for the InGaN/GaN material system were taken from [12] and [13,14], respectively. It is shown that IQE decreased by ~45% for blue (peak wavelength = 470nm), and by ~70% for green (peak wavelength = 550nm) when the µLED chip size was reduced from 200µm to 5µm.…”
Section: Micro Led Efficiency Versus Chip Sizementioning
confidence: 99%
“…Experimental data and theoretical predictions of "planar" InGaN/GaN µLEDs' normalized maximum IQE as a function of µLED size. For theoretical lines, the ABC model was used with model parameters taken from [12][13][14].…”
Section: Micro Led Efficiency Versus Chip Sizementioning
confidence: 99%
“…Nevertheless, quantum efficiency of µLEDs is yet a challenging subject when dealing with high luminance levels. Besides, µLED size dependence has been thoroughly studied and reported in literature, but mostly for blue color emitting ones 4,5 . A lack of comprehension of size effect is then still to be filled for these green light-emitting diodes dedicated to specific µ-displays applications.…”
Section: Introductionmentioning
confidence: 99%